Anticipation of thermal pain in diverticular disease - Smith, Jan K.; Marciani, Luca; Humes, David J.; Francis, Susan T.; Gowland, Penny A.; Spiller, Robin C. (Wiley, 2016)
Background The relative importance of peripheral nerve injury or differences in central pain processing in painful diverticular disease (DD) is unclear. Functional MRI has demonstrated changes in the anticipation of pain in irritable bowel syndrome (IBS), in whom dysfunctional central pain pro-cessing predominates. This study aims to identify anticipatory changes in Symptomatic DD (SDD) compared to asymptomatic DD (ADD) and IBS patients. Methods Cued painful cutaneous thermal stimuli were delivered to the left hand and foot of ADD, SDD or IBS patient groups during functional MRI. Gastrointestinal symptoms and somatization, via the physiological heath question 12 (PHQ12-SS) were evaluated. The SDD group was divided into 2 based on a PHQ12-SS score of ≤6 (low somatization: LSDD) or ≥7 (high somatization: HSDD). Fixed effect group analysis of the ‘cued’ anticipatory phase was performed. Key Results 74 participants were recruited to the study. After exclusions for excessive movement and incom-plete study data, 14 participants per group (IBS, ADD, LSDD and HSDD) were analysed and compared. Within the right posterior insula (pINS), a key somatosensory pain processing area, greater deactivation was found in the ADD compared to the LSDD, IBS and HSDD groups. In emotion processing centres, such as the anterior and middle insula (aINS and mINS), greater ac-tivation was identified in the LSDD, IBS and HSDD groups compared to the ADD group and in the LSDD compared to IBS and HSDD groups. Differences in left ACC activation were also seen between the LSDD and HSDD groups. In comparison the amygdala (AMYG) and/or hip-pocampal deactivation was greater in the ADD than the IBS and HSDD group and between the low and high somatising SDD groups. Altered descending nociceptive control centres also showed greater deactivation such as the medial frontal gyrus (which includes the dorsolateral prefrontal cortex, DLPFC) and orbito-frontal cortex in the ADD and the LSDD group compared to the HSDD and IBS groups. Conclusion & Inferences The high somatising SDD group have altered anticipatory responses to thermal pain, behaving similar to IBS group. The low somatising SDD are similar to ADD group. This suggests underly-ing differences in pain pathophysiology, and the need for individualized treatment strategies to target the cause of their chronic pain.